Estimation of genetic parameters and phenotypic and genetic trends of the calving interval in the Mambi de Cuba cattle and its relation with the milk yield - Hern?ndez, Arelis; Ponce de Le?n, Raquel; Garc?a, Sonia M.; Guzm?n, Gladys; Mora, Marta (Cuban Journal of Agricultural Science, 2011)
In order to estimate the genetic parameters and the phenotypic and genetic trends of the CI and its relationship with the MY305, 16 526 records of the calving interval (CI) and the milk yield accumulated up to 305 d (MY305) of 5 881 Mamb? de Cuba cows (? Holstein ? Zebu), were used. The records were from four cattle units and 171 herds. The records corresponded to the period of 1981- 2006. An univariate animal model was used, including as fixed effects the combination herd-year-calving period of four months; calving age, as linear and quadratic covariable, and as random effects the animal, the permanent environment and the residuals, to estimate the heritability and the repeatability of the CI. A bivariate animal model was applied to estimate the genetic and environmental correlation between the CI and the MY305. The estimates of heritability and repeatability for the CI were of 0.06 ? 0.01 and 0.20 ? 0.01, respectively. The phenotypic trend for the CI was of 3.13 ? 1.12 days.year-1 and the genetic trend of -1.53 ? 0.16 days.year-1. The genetic and environmental correlations between the CI and the MY305 were of 0.72 ? 0.06 and 0.01 ? 0.01, respectively. It was concluded that the increase in the phenotypic trend for the CI in the Mambi de Cuba cattle was explained by environmental causes and not by the deterioration in the genetic merit. The correlation between the CI and the MY305 was opposite, thus, the increment in the capacity of milk yield of the cows will reduce the reproductive efficiency of the herd. Key words: Mambi de Cuba cattle, calving interval, genetic parameters, genetic trends, correlation with the milk yield.